2021
DOI: 10.1088/1367-2630/ac430b
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hermiticity-induced reentrant localization in a quasiperiodic lattice

Abstract: In this paper, we demonstrate that the non-Hermiticity can induce reentrant localization in a generalized quasiperiodic lattice. Specifically, by considering a nonreciprocal dimerized lattice with staggered quasiperiodic disorder, we find that the localization transition can appear twice by increasing the disorder strength. We also unravel a multi-complex-real eigenenergy transition, whose transition points coincide with those in the localization phase transitions. Moreover, the impacts of boundary conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 76 publications
0
5
0
1
Order By: Relevance
“…It was shown that an intermediate regime characterized by the coexistence of localized and extended states at different energies may occur 3,4 . The theoretical findings were confirmed in an experimental realization of a system with a single-particle mobility edge 5 .Recently, in non-Hermitian systems mobility edges have been explored for various 1D tight-binding models [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . In non-Hermitian systems, in comparison to the Hermitian ones, the mobility edges not only separate localized states from the extended states but also indicate the coexistence of complex and real energies.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…It was shown that an intermediate regime characterized by the coexistence of localized and extended states at different energies may occur 3,4 . The theoretical findings were confirmed in an experimental realization of a system with a single-particle mobility edge 5 .Recently, in non-Hermitian systems mobility edges have been explored for various 1D tight-binding models [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . In non-Hermitian systems, in comparison to the Hermitian ones, the mobility edges not only separate localized states from the extended states but also indicate the coexistence of complex and real energies.…”
mentioning
confidence: 69%
“…Recently, in non-Hermitian systems mobility edges have been explored for various 1D tight-binding models [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . In non-Hermitian systems, in comparison to the Hermitian ones, the mobility edges not only separate localized states from the extended states but also indicate the coexistence of complex and real energies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-Hermitian physics has attracted extensive attention, as non-Hermitian Hamiltonian can be used to explore the properties of open systems, quantum systems with gain and loss, as well as various classical systems [1][2][3][4][5][6][7][8][9][10][11]. In general, the energy band structure of non-Hermitian systems is complex, except for certain systems with pseudo-Hermiticity and parity-time (PT ) symmetry [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, growing effort has recently been made to explore topological and localization physics in non-Hermitian Hamiltonians or systems [80][81][82][83][84][85][86][87][88][89][90]. For instance, in the presence of non-Hermiticities from nonreciprocal hopping [63,[91][92][93][94] or complex on-site potential [69,[93][94][95][96][97], it has been revealed that topological phase transition characterized by a spectral winding number coincides with localization transition and (or) real-complex transition [63,69,79,97,98]. The non-Hermitian quasiperiodic systems may exhibit generalized mobility edge [93,96].…”
Section: Introductionmentioning
confidence: 99%